2016
DOI: 10.1021/acs.macromol.6b01086
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Intracrystallite and Intercrystallite Limitations of Charge Transport in Polythiophenes

Abstract: Charge carrier mobilities in conjugated semicrystalline polymers depend on morphological parameters such as crystallinity, crystal orientation, and connectivity between ordered regions. Despite recent progress in the development of conducting polymers, the complex interplay between the aforementioned parameters and their impact on charge transport is not fully understood. By varying the casting solvents and thermal annealing, we have systematically modulated the crystallization of poly(3-hexylthiophene-2,5-diy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
59
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 94 publications
7
59
1
Order By: Relevance
“…Finally, we find that the effective activation energies, which govern the temperature dependence of charge mobility as μ(T)=μ0eEa/kT, are the same for charge transport in both the π–π stacking and backbone directions. The value of E a is about 100 meV, consistent with reported values, ranging from 23 to 116 meV . The Arrhenius dependence of mobility also indicates that the mechanism of charge transport in P3HT may be thermally activated hopping and the Marcus theory–based model is valid.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Finally, we find that the effective activation energies, which govern the temperature dependence of charge mobility as μ(T)=μ0eEa/kT, are the same for charge transport in both the π–π stacking and backbone directions. The value of E a is about 100 meV, consistent with reported values, ranging from 23 to 116 meV . The Arrhenius dependence of mobility also indicates that the mechanism of charge transport in P3HT may be thermally activated hopping and the Marcus theory–based model is valid.…”
supporting
confidence: 88%
“…Combining MD results with a site‐to‐site charge hopping model, we demonstrate the effect of thermal fluctuations on charge mobility for crystalline P3HT. Previous works have suggested that charge carriers may be strongly localized and the temperature dependence of charge mobility is Arrhenius for P3HT . We treat charge transport in crystalline P3HT as 2D random hopping processes in both the backbone and π–π stacking directions.…”
mentioning
confidence: 99%
“…The formation of such physical connections depends on the polymer chain contour length, the polymer chain persistence length, and the characteristic spacing between neighboring ordered regions . For such purposes, polymers with high MWs and high crystallinity are needed. And, as described above, polymers with rigid coplanar backbones have higher persistence length, which should in turn also facilitate the formation of tie chains …”
Section: Opportunities For Improving Charge Transportmentioning
confidence: 99%
“…, Copyright (2013). (e) Percolation pathway formed by a tie chain between adjacent lamellae . (f) Higher molecular weight polymers have a higher probability of forming tie chains .…”
Section: A Percolated Crystal Morphology For High Performancementioning
confidence: 99%